An Unusual Case of Desmoplastic Melanoma Containing an Osteoclast-like Giant Cell-Rich Nodule. (April 2015) - Houang, Michelle; Castillo, Christine; La Marca, Sophie; Combemale, Patrick; Wang, Qing; Paindavoine, Sandrine; Pissaloux, Daniel; de la Fouchardiere, Arnaud
Abstract : Abstract: The authors describe a case of a 5 cm mixed desmoplastic melanoma occurring on the cheek of an 88-year-old white woman. The epidermis showed the features of lentigo maligna. Within the dermis, there was a mixed desmoplastic melanoma with 2 components. The first component consisted of infiltrative malignant spindled cells with prominent stromal fibrosis and had the typical appearance of desmoplastic melanoma. The second component was within the deep half of the tumor and consisted of a densely cellular nodule composed of spindled melanocytes admixed with many osteoclast-like giant cells. There was a peripheral neurotropism and tumor invaded bone. The Breslow thickness was 14 mm. On follow-up, a sacral metastasis was discovered, which had a similar morphology to the deep cellular nodule. Immunohistochemistry of spindled cells both inside and outside the nodule showed S100 positivity with the absence of other melanocytic markers (HMB-45, Melan-A). Smooth muscle actin and p63 were focally positive. The osteoclast-like giant cells expressed CD68 and MiTF. Array comparative genomic hybridization of the typical desmoplastic melanoma region had a flat profile, whereas the cellular osteoclast-like giant cell–rich region displayed important cytogenetic anomalies, some of which have been previously described in melanomas. The main array comparative genomic hybridization findings were confirmed by fluorescence in situ hybridization using specific probes. The differences in morphology and molecular cytogenetics between the 2 areas suggest that these might represent the progression or emergence of a more aggressive clone within the tumor. Subsequent metastatic spread to the bone may be a result of accumulated cytogenetic abnormalities.